Stay in the U.S. or Return to China: Push-Pull Factors Influencing International Students’ Choices During COVID-19 (Comparative & International Education Series, 2021)
This article, based on in-depth interviews with 11 Chinese students studying in the U.S., examines the factors that have influenced their decisions to return to China or stay in the U.S. during the COVID-19 pandemic. Influencing issues are classified into push, pull, reverse push, and reverse pull factors to demonstrate their origins and effects. The results reveal that students’ choices are mainly influenced by the increasing cases in the U.S. and the travel bans in both countries, but they also take other economic, social, and academic factors into consideration. Suggestions for government and institutions are offered to protect international students’ benefits.